Novel high gain DC–DC converter based on coupled inductor and diode capacitor techniques with leakage inductance effects. Issue 11 (18th June 2020) - Hoseinzadeh Lish, Mana; Ebrahimi, Reza; Madadi Kojabadi, Hossein; Guerrero, Josep M.; Nourani Esfetanaj, Naser; Chang, Liuchen
Abstract : In this study, due to the low output voltage that often is presented by renewable energy sources like photovoltaic panels, a single switch high step‐up dc–dc converter with high efficiency is proposed. The presented step‐up dc–dc converter uses a coupled inductor and diode‐capacitor technique to achieve high voltage gain. By changing the turns ratio of the coupled inductor, this novel topology does not need to operate at a high duty cycle conditions to obtain the high voltage gain. Moreover, the leakage inductance energy of the coupled inductor is recovered by using two passive clamp circuits to reduce the stress across the semiconductor devices, which improve efficiency. The operating modes of the proposed converter and the theoretical analysis are considered and finally, a prototype setup has been implemented to accredit the accuracy of the theoretical and simulation analysis.